Epidemiological and Diagnostic Aspects of Bladder Bilharziomas in the Urology Department of Idrissa Pouye General Hospital (HOGIP) - Oumar Gaye; Mohamed Jalloh; Ngor M Thiam; Medina Ndoye; Khadidiatou Dansokho; Youssef Bellamine; Saint C. N Kouka; Cherif Dial; Mouhamadou M Mbodji; Ayun Cassell; Issa Labou; Lamine Niang; et al. (Advances in Urology)
Objective. The aim of our study is to assess the diagnostic aspects of bladder bilharzioma in the Urology Department of Idrissa Pouye General Hospital (Senegal). Materials and Methods. It is a descriptive study from January 2013 to December 2018. The patients included in the study were those who had anatomopathological examination of bladder biopsy that showed a schistosomiasis pseudotumor of the bladder. The variables studied were sociodemographic, clinical symptoms, imaging findings, histology, and treatment. The data have been saved and analyzed by the 2013 Excel software. Results. Thirteen patients were included in our study. The average age was 27 ± 12.1 years. Sex ratio was 1.6. The majority of the patients were from the northern part of Senegal. Hematuria was the main symptom for all the patients. Cystoscopy was performed for all the patients and showed 5 granulomas and 8 fibrocalcic polyps. A transurethral resection of the bladder was performed, and treatment with praziquantel (40 mg/kg of bodyweight) has been carried out. One patient presented precancerous lesions such as metaplasia and dysplasia of the bladder mucosa. After a median follow-up of 40 months (6–57 months), ten patients had a favorable clinical and endoscopic outcome. Conclusion. Granulomas and fibrocalcic polyps of the bladder mucosa are, respectively, confused with squamous cell carcinoma and bladder lithiasis in endemic areas of schistosomiasis. Good cystoscopy interpretation can provide the diagnosis of bladder bilharzioma and start the treatment.